Area of lily leaf beetle Lilioceris lilii Scopoli, 1763 (Coleoptera: Chrysomelidae: Criocerinae) - M.Ja. Orlova-Bienkowskaja (Кавказский энтомологический бюллетень, 2012)
A distribution map is provided for Lilioceris lilii (Scopoli, 1763) (Coleoptera: Chrysomelidae). 343 localities in the Nearctic and Palaearctic, including 146 localities in Russia, are shown. Examination of old collections of Zoological Institute (St. Petersburg), Zoological Museum of Moscow State University and analysis of literature revealed, that this species did not occur in northern and central regions of European Russia before 1898, but inhabited European countries, south regions of European Russia (as far north as Voronezh), Siberia and Far East. Now it is a common pest in northern and central regions. L. lilii occurs in following regions of Russia: Altai Prov.*, Altai Republic*, Amur Region, Bashkortostan*, Bryansk Region*, Buryatia*, Chelyabinsk Region, Chuvashia, Irkutsk Region, Ivanovo Region*, Jewish Autonomous Region, Kaliningrad Region, Kaluga Region*, Kemerovo Region*, Khabarovsk Prov.*, Khakassiya, Khanty-Mansi Autonomous Area*, Kirov Region, Kostroma Region*, Krasnodar Prov.*, Krasnoyarsk Prov., Kurgan Region, Kursk Region, Leningrad Region, Lipetsk Region, Moscow Region, Nizhny Novgorod Region*, North Ossetia*, Novosibirsk Region*, Omsk Region*, Orel Region*, Orenburg Region, Penza Region*, Primorski Prov.*, Pskov Region, Samara Region, Saratov Region*, Sverdlovsk Region*, Tatarstan, Tomsk Region*, Transbaikal Prov.*, Tula Region*, Tyumen Region*, Udmurtia, Ulyanovsk Region, Vladimir Region*, Volgograd Region*, Voronezh Region*, Yakutia, Yaroslavl Region (first records are indicated with an asterisk*).